2020
DOI: 10.1136/rmdopen-2020-001297
|View full text |Cite
|
Sign up to set email alerts
|

Probability-based algorithm using ultrasound and additional tests for suspected GCA in a fast-track clinic

Abstract: ObjectivesClinical presentations of giant cell arteritis (GCA) are protean, and it is vital to make a secure diagnosis and exclude mimics for urgent referrals with suspected GCA. The main objective was to develop a joined-up, end-to-end, fast-track confirmatory/exclusionary, algorithmic process based on a probability score triage to drive subsequent investigations with ultrasound (US) and any appropriate additional tests as required.MethodsThe algorithm was initiated by stratifying patients to low-risk categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
2
29
2
4
Order By: Relevance
“…The specific diagnoses in patients not classified as suffering from cGCA are listed in Table S1 of the Supplementary Materials . Logistic regression analysis substantiated the results of the literature review [ 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], showing that a model including jaw claudication (logOR 4.1, 95% CI 1.7–6.7), new onset permanent headache (logOR 3.5, 95% CI 0.6–4.8), age > 70 (logOR 2.2, 95% CI 0.03–4.4), and an ophthalmological diagnosis of anterior ischemic optic neuropathy (AION; unilateral: logOR 2.7, 95% CI 0.6–4.7; bilateral: logOR 3.5, 95% CI 0.07–6.8) discriminated patients with and without cGCA with the highest diagnostic accuracy (AIC 48.6; area under the curve (AUC) 0.96).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The specific diagnoses in patients not classified as suffering from cGCA are listed in Table S1 of the Supplementary Materials . Logistic regression analysis substantiated the results of the literature review [ 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], showing that a model including jaw claudication (logOR 4.1, 95% CI 1.7–6.7), new onset permanent headache (logOR 3.5, 95% CI 0.6–4.8), age > 70 (logOR 2.2, 95% CI 0.03–4.4), and an ophthalmological diagnosis of anterior ischemic optic neuropathy (AION; unilateral: logOR 2.7, 95% CI 0.6–4.7; bilateral: logOR 3.5, 95% CI 0.07–6.8) discriminated patients with and without cGCA with the highest diagnostic accuracy (AIC 48.6; area under the curve (AUC) 0.96).…”
Section: Resultssupporting
confidence: 63%
“…Of note, Laskou et al were the first to use a clinical reference diagnosis, taking into account the clinical course over time [ 28 ]. Subsequently, this Southend pretest probability score, stratifying fast-track referral patients into low-risk, intermediate-risk, and high-risk probability categories based on 17 items, was shown to enhance the test performance of temporal/axillary artery sonography [ 29 ]. Most recently, a Canadian study contextualized the diagnostic yield of temporal artery magnetic resonance angiography in the diagnosis of GCA dependent on pre-test-probability [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason could be that occlusion and stenosis are not assessed routinely, as mentioned in OMERACT, and more work is certainly needed to standardize the definition of these findings. A recent study showed that when combining the GCA pre-test probability score with the halo sign, the sensitivity increases to between 94 and 100% [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that imaging test results should always be interpreted in the context of the level of suspicion of GCA, which is generally based on the clinical judgment and experience of the physician treating patients with GCA. Efforts have been made by different expert groups to develop pre-test clinical probability scores for GCA to help clinicians estimate the likelihood of GCA [65,66]. These scores can be potentially useful in ensuring a more homogeneous management of patients with GCA and in optimizing the performance of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%